Applications of texturization techniques on cutting tools surfaces-a survey - Fonteque Ribeiro, Fernando Sabino [UNESP]; Lopes, Jose Claudio [UNESP]; Bianchi, Eduardo Carlos [UNESP]; Angelo Sanchez, Luiz Eduardo de [UNESP] (Springer, 2020)
The development of manufacturing processes advances in productivity and cost reduction. Industry 4.0 increasingly allows production to be automated, eliminating production errors and allowing the manufacture of mechanical components with complex geometries. However, the chip formation mechanisms are still the same, generating friction and heat during machining aided by the machining resistant materials and higher cutting speeds. The evolution in materials for cutting tools and hard coatings, as well as efficient techniques for the application of cutting fluid, has been the focus of numerous researches in the field of machining. To obtain better machining conditions, the functionalization of surfaces, through the texturing of micro and nano-geometries on the rake and flank faces of cutting tools, has proven to be effective and promising. This technique increases the entry and retention of the cutting fluid in the contact zones. It reduces the contact area between chip and tool in dry cutting, allowing less friction at the chip-tool interface, reduction in machining temperatures, lower adhesion, and longer tool life. The present work aims to relate the application of textured cutting tools according to the machining materials and cutting tools found in scientific articles of high relevance. Thus, the review refers to the implementation of textured cutting tools in nickel-based alloys, titanium alloys, medium carbon steels, and aluminum alloys, as well as pointing out recent research on cutting tool materials, hard coatings, and solid lubricants applied on textured cutting tools.
Keywords: Textured cutting tools; Tool life; Friction; Temperature; Cutting forces